Management of competitive sport at historically disadvantages Universities in South Africa - Matlala, Philemon Kgaudi. (My University, 2001)
Refer to document
Thesis (M.Dev.) -- University of Limpopo, 2001
Keywords: Sports administration; University sports; Sports - South Africa; College sports - South Africa - Organization and administration